2016
DOI: 10.1097/nne.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Development Through Case Study and Simulation

Abstract: Because empathy is integral to the nurse-patient relationship, nurse educators are challenged to explore teaching strategies that may aid in the development of empathy among students. The purpose of this study was to determine whether consistent exposure to a single patient through case study and simulation had an impact on empathy levels in senior-level baccalaureate nursing students. Results provide interesting conclusions for faculty members and offer a basis for ongoing discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…Eight of the conceptual papers (Dinkins, ; Hunt et al, ; Irving & Dickson, ; Latimer et al, ; Määttä, ; Marcysiak et al, ; McKinnon, ; Wiseman, ) and ten of the education papers (Beddoe & Murphy, ; Cunico et al, ; Everson et al, , ; Finch, ; Haley et al, ; Lee et al, ; Levett‐Jones et al, ; Lobchuk et al, ; Mennenga et al, ) referred to affective empathy. It was described as the ability to perceive or “read” the meanings and feelings associated with a person's experience (Wiseman, ), and to perceive and subjectively experience another person's emotions (Beddoe & Murphy, ; Everson et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of the conceptual papers (Dinkins, ; Hunt et al, ; Irving & Dickson, ; Latimer et al, ; Määttä, ; Marcysiak et al, ; McKinnon, ; Wiseman, ) and ten of the education papers (Beddoe & Murphy, ; Cunico et al, ; Everson et al, , ; Finch, ; Haley et al, ; Lee et al, ; Levett‐Jones et al, ; Lobchuk et al, ; Mennenga et al, ) referred to affective empathy. It was described as the ability to perceive or “read” the meanings and feelings associated with a person's experience (Wiseman, ), and to perceive and subjectively experience another person's emotions (Beddoe & Murphy, ; Everson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine of these studies used single-group pretest post-test designs (Beddoe & Murphy, 2004;Everson et al, 2015Everson et al, , 2018Finch, 2016;Mete, 2007;Nosek, Gifford, & Kober, 2014;Ozcan, Bilgin, & Eracar, 2011;Sheehan, Perrin, Potter, Kazanowski, & Bennett, 2013;Ward, Cody, Schaal, & Hojat, 2012) and two studies used post-test only designs (Lobchuk et al, 2016;Strekalova, Krieger, Kleinheksel, & Kotranza, 2017). One of the studies was a randomized controlled trial (Haley et al, 2017) and the remaining six were case-control studies (Cunico, Sartori, Marognolli, & Meneghini, 2012;Henry, Ozier, & Johnson, 2011;Lee, Yu, Hsieh, Li, & Chao, 2018;Levett-Jones et al, 2017;Mennenga, Bassett, & Pasquariello, 2016;Webster, 2010), with each of them testing changes in empathy after an educational intervention and/or comparing empathy outcomes with those of a control group. The included studies were conducted in eight countries: 10 in the USA, two in Turkey, three in Australia, and one each from Canada, Italy and Taiwan.…”
Section: Educational (Secondary) Studiesmentioning
confidence: 99%
“…11,12,14 The results of this study, demonstrating an increase in student empathy following activity completion, are congruent with others examining changes in learner empathy towards patients in differing scenarios. [11][12][13][14][15][16][17][18] However, certain limitations should be considered when drawing conclusions from this study. While student empathy appeared to increase following the simulation, most of the survey items did not demonstrate statistically significant changes.…”
Section: A J P Ementioning
confidence: 99%
“…Evidence has shown that experiential education and active learning exercises, such as simulations, are effective tools to instill empathy in students enrolled in nursing, physician, and pharmacy coursework. [11][12][13][14][15][16][17][18] As TOC is an evolving topic in health care, few studies to date have been conducted to detail how this subject should be incorporated into health education curricula, or how students perceive the hardships of patients transitioning from one health care setting to another with limited resources or social support.…”
Section: Introductionmentioning
confidence: 99%
“…McKenna and colleagues find that nursing students have an "acceptable level" of empathy, although the study points to room for improvement (McKenna et al, 2012). Both studies draw their conclusions on the basis of statistical data, hence illustrating the inclination to approach empathy as an, inner, psychological and measurable matter (see also Mennenga et al, 2016).…”
Section: Introductionmentioning
confidence: 98%